Measuring the Content Characteristics and Ad Efficacy of GoJek and Grab advertisement. - Rasun, Gerald Kristianto; Aprilianty, Fitri (Journal of Business and Management, 2020)
Abstract. GoJek and Grab are a company here in Indonesia that move on the Ride Hailing Transportation Service industry. They compete on almost every aspect in their businesses, one of those aspects is the advertisement. The problem is they adopt different strategies in their advertisement, even though they are in the same industry. This brings the question of which advertisement strategies are more effective to attract the customer. There is a statement in previous research that in order to analyze the effectiveness of an Advertisement, researchers could measure the Content Characteristics and Ad Efficacy of the advertisement itself. The researcher used the quantitative approach in order to gain the data that is needed for this research, by handing out surveys in the form of questionnaires to the sample of this research. Researchers use the Kruskal Wallis and the SmartPLS test to analyze the data from the survey. The main purpose of this study is to give recommendations for companies or businesses on the Ride Hailing Transportation Service industry on their advertisement strategy.Keywords: Ad Efficacy, Advertisement, Advertisement Strategy, Content Characteristics, Effective Advertisement